PRODUK KOSMETIK PALSU: MINAT PEMBELIAN BERDASARKAN PENGARUH FAKTOR SOSIAL DAN FAKTOR PRIBADI - Utama, Satria Putra; Sari, Risca Kurnia; Mahardhani, Ahmad Subhan (LP2M Institut Teknologi dan Bisnis Asia Malang, 2021)
The rapidly growing cosmetic industry has caused intense competition for both legal and illegal cosmetic products. The purpose of this study is to analyze and measure the influence of social factors on interest in buying and using fake cosmetic products, explore the basic causes of consumers buying and using fake cosmetic products, and measure the influence of personal factors on interest in buying and using fake cosmetic products in the city community. Poor. This type of research is a survey research, namely research that takes a sample from a population and uses a questionnaire as the main data collection instrument. Thus, this research is categorized as explanatory research. The number of respondents in this study were 100 people. The research sample was taken using purposive sampling technique. The data collection method used is a questionnaire method, then the data is processed through SPSS software. The analytical tool in this study uses linear regression.